Long-Term GAD-alum Treatment Effect on Different T-Cell Subpopulations in Healthy Children Positive for Multiple Beta Cell Autoantibodies - Falastin Salami; Lampros Spiliopoulos; Marlena Maziarz; Markus Lundgren; Charlotte Brundin; Rasmus Bennet; Magnus Hillman; Carina Törn; Helena Elding Larsson (Journal of Immunology Research)
Objective. The objective of this study was to explore whether recombinant GAD65 conjugated hydroxide (GAD-alum) treatment affected peripheral blood T-cell subpopulations in healthy children with multiple beta cell autoantibodies. Method. The Diabetes Prevention–Immune Tolerance 2 (DiAPREV-IT 2) clinical trial enrolled 26 children between 4 and 13 years of age, positive for glutamic acid decarboxylase autoantibody (GADA) and at least one other autoantibody (insulin, insulinoma antigen-2, or zinc transporter 8 autoantibody (IAA, IA-2A, or ZnT8A)) at baseline. The children were randomized to two doses of subcutaneously administered GAD-alum treatment or placebo, 30 days apart. Complete blood count (CBC) and immunophenotyping of T-cell subpopulations by flow cytometry were performed regularly during the 24 months of follow-up posttreatment. Cross-sectional analyses were performed comparing lymphocyte and T-cell subpopulations between GAD-alum and placebo-treated subjects. Results. GAD-alum-treated children had lower levels of lymphocytes (109 cells/L) (p=0.006), T-cells (103 cells/μL) (p=0.008), T-helper cells (103 cells/μL) (p=0.014), and cytotoxic T-cells (103 cells/μL) (p=0.023) compared to the placebo-treated children 18 months from first GAD-alum injection. This difference remained 24 months after the first treatment for lymphocytes (p=0.027), T-cells (p=0.022), T-helper cells (p=0.048), and cytotoxic T-cells (p=0.018). Conclusion. Our findings suggest that levels of total T-cells and T-cell subpopulations declined 18 and 24 months after GAD-alum treatment in healthy children with multiple beta-cell autoantibodies including GADA.